2010
DOI: 10.1007/s12583-010-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Well logging responses of UHP metamorphic rocks from CCSD main hole in Sulu terrane, eastern central China

Abstract: The lithologies of the Chinese Continental Scientific Drilling main hole (CCSD-MH) are mainly comprised of orthogneiss, paragneiss, eclogite, amphibolite, and ultramafic rocks. The statistical results of logs of CCSD-MH indicate that ultramafic rocks are characterized by very high CNL (neutron log) and very low GR (gamma ray log) and RD (resistivity log); eclogites are characterized by high DEN (density), V P (P-wave velocity) and PE (photoelectric absorption capture cross section); orthogneiss and paragneiss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Metal mineral content of ultramafic rock (Fe 2 O 3 is 5.81%-8.12%; FeO is 2.8%-6.11%) of the CCSD-MH is a little higher than those of the other rocks Zhang et al, 2006b), so its resistivity is relatively low. The neuron log shows that the hydrogen content of ultramafic rock of CCSD-MH is high (Luo and Pan, 2010), because the ultramafic rock is serpentinized peridotite . Therefore, the serpentinized effect may cause the increase of metal mineral and hydrogen content and the decrease of resistivity.…”
Section: Analysis Of Resistivity Logsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal mineral content of ultramafic rock (Fe 2 O 3 is 5.81%-8.12%; FeO is 2.8%-6.11%) of the CCSD-MH is a little higher than those of the other rocks Zhang et al, 2006b), so its resistivity is relatively low. The neuron log shows that the hydrogen content of ultramafic rock of CCSD-MH is high (Luo and Pan, 2010), because the ultramafic rock is serpentinized peridotite . Therefore, the serpentinized effect may cause the increase of metal mineral and hydrogen content and the decrease of resistivity.…”
Section: Analysis Of Resistivity Logsmentioning
confidence: 99%
“…Niu et al (2004) briefly introduced the well logging methods performed at the CCSD-MH (100-2 000 m) and some preliminary studies they have finished. The well logs of the entire borehole were displayed and analyzed in several references (Luo and Pan, 2010;Luo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These occur in a range of continental and oceanic settings, where a number of boreholes have been and continued to be drilled in order to provide information of the Earth's crust by means of geophysical surveys and geological mapping (Harvey et al, 2005). Several studies have been reported by geophysicists based on crystalline rocks using well logging data (see for example Pratsone et al, 1992;Pechnig et al,1997Pechnig et al, , 2005Bartetzko et al, 2005;Maiti and Tiwari, 2009;Luo and Pan, 2010;. The general understanding collected from these studies show that, the well logging data from crystalline rocks are not simple to analyze because of their complicated geological characteristics and the difficulty in understanding and using the intensive information content in these data.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al (2009) constructed the lithology recognition model combining the logging response and several well logs of different rocks with the method of cluster analysis and stepwise discriminant analysis. Luo and Pan (2010) used core-log correlation and cross-plotting methods, and the results allowed the authors to conclude that the lithology is mainly comprised orthogneiss, paragneiss, eclogite, amphibolite, and ultramafic rocks. Bosch et al (2013) used fuzzy logic for lithology prediction from well log data of the German Continental Deep Drilling Program (KTB).…”
Section: Introductionmentioning
confidence: 99%